Language Acquisition in Children Aged 2 Years 8 Months Study of Mean Length of Utterance MI Negeri 5 Kuningan - Estiawati; Meiliya, Eti (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to examine language acquisition in children aged 2 years 8 months through the analysis of Mean Length of Utterance. MLU is one of the important indicators in measuring the development of children's morphosyntactics, which is calculated based on the average number of morphemes in each utterance. This study uses a qualitative descriptive approach with a case study method. The subject of the study was a child aged 2 years 8 months who was in a family environment with Indonesian as the main language interaction. Data were collected through direct observation and recording of children's language activities in natural situations, then analyzed using transcription techniques and MLU calculations based on the rules set by Brown (1973). The results of the study showed that the child's MLU was in the range of X.X (fill in according to the data later), which indicates that the child has reached the stage of language sentence development that is appropriate for his age, with the characteristics of using simple structures and the beginning of the development of the use of bound morphemes. These findings provide an illustration that a rich and interactive language environment contributes to children's language acquisition in the early stages of life.